Enhancing MSME Capability through Digital Marketing Education and the Role of University Facilitators in Bandung City - Asti Nur Aryanti; Christianingrum Christianingrum; Widyastuti Nurmalia Utami; Palupi Permata Rahmi; Shintia Permata (CV. Tripe Konsultan, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in regional economic development. However, many MSMEs still face limitations in digital marketing capability, particularly in utilizing social media, marketplaces, and online promotion strategies. This study aims to analyze the effect of digital marketing education programs on improving MSME capabilities in Bandung City. The research employs a quantitative approach using a pretest–posttest design supported by secondary data from the Central Statistics Agency. The findings indicate that digital marketing education significantly improves MSME capability, particularly in content creation, social media management, and marketplace optimization. The study recommends practice-based education and continuous mentoring to strengthen MSME competitiveness in the digital economy.